Study Of Clinico-Histopathological Correlation of Seborrheic Keratosis - Jakasania, Dharti Durlabhjibhai; Shah, Shaila N (Annals of Pathology and Laboratory Medicine, 2019)
Background: Seborrheic keratosis (SK) is one of the mostcommon epidermal tumors of the skin. However, only a few large-scale clinic-histopathological investigations have been conducted on SK or on the possible correlation be-tween histopathological SK subtype and location. The aim of this study was to analyze the clinical and histopathological features of a relatively large number of cases of diagnosed SK. Methods: Seventy five (75) pathology slides of skin tissue from patients with clinically diagnosed SK and 67 cases of biopsy-proven SK were analyzed. The biopsy-proven cases of SK were assessed for histopathological subclassification. The demographic, clinical, and histopathological data of the patients were collected for analysis of associated factors. Result: Seborrheic keratosis commonly present in old age most common age group is 60-70 yr. It affects male and female equally (M:F-1.12:1).Most common etiology in our study is sun exposure. In our study upper extremities are most commonly involved.Among histologically proven 67 cases most common histological type in our study is clinical seborrheic keratosis(CSK) (68.65%) followed by stucco keratosis (23.88%). Among common seborrheic keratosis hyperkeratotic type (31.34%) is most common followed by melanoacanthoma (19.40%).Histopathologically proven cases of seborrheic keratosis shows significant presence histopathological features like hyperkeratosis (69.33%), acanthosis (66.66%) and papillomatosis(60%). Hyperpigmentation is also present in significant number of cases (34.66%). Conclusion: SK appear to be more common in old-age, with equal sex distribution, predominantly affecting the upper extremities, head, and neck. Sun exposure was the most common etiology. The most frequent SK histopathological sub-type found in this study was the clinical seborrheic keratosis followed by stucco keratosis. In clinical seborrheic keratosis most common variant was hyperkeratotic type followed by melanoacanthoma. Most of the characteristics of SK are in accordance with the literature published.